DIGITAL FINANCIAL LITERACY TRAINING FOR YOUTH OF NORTHWEST HAGU VILLAGE USING CAPITAL MARKET INVESTMENT AND STOCK SAVINGS METHODS - Muhammad Multazam; Rico Nur Ilham; Irada Sinta; Muttaqien; Ayu Anora; Yusnidar (RADJA PUBLIKA, 2024)
Digital financial literacy training for the youth of Gampong Hagu Barat Laut aims to improve their understanding of capital market investment and stock saving strategies. This activity is designed to introduce the basic concepts of digital finance, especially in relation to capital market investment, which is often considered a tool for achieving long-term financial stability. With the capital market investment and stock saving methods, training participants are invited to understand the risks and benefits associated with long-term investment and portfolio diversification. In this training, emphasis is placed on the importance of stock saving discipline, where young people are expected to be able to consistently set aside funds to be invested, even in small amounts, but done sustainably. This training also emphasizes the use of safe and legal digital financial platforms, so that participants can take advantage of technological advances to invest efficiently and transparently. The results of the training showed an increase in the knowledge and skills of participants in understanding how the capital market operates, as well as how to start investing in stocks safely and profitably. Young people who were previously unfamiliar with the capital market now have basic knowledge that allows them to be more actively involved in investment activities, as a step to improve their financial literacy and strengthen their personal and community economy.